A Pilot Study on the Efficacy of Stress Relief Programs for Family Caregivers of Older People with Dementia. (1st September 2020) - Tsai, Pi-Lan; Chan, Shu-Min; Jiang, Ru Shang; Lee, Shwu-Hua; Hsu, Jung Lung
Abstract: The aim of this study was to evaluate the effects of stress-relief programs on positive aspects of caregiving and depression among caregivers of older people with dementia. A quasi-experimental design was employed. Participants in the experimental group received a 8-week period and 120 minutes each session cognitive-behavioral therapy. Participants in the control group received standard health education. Stress relief programs may alleviate depression and increase positive aspects of caregiving among family caregivers of older people with dementia. These findings will help health professionals to implement stress-relief strategies for family caregivers of older people with dementia, or to use those strategies to increase positive aspects of caregiving, or to alleviate depression in caregivers.